Higher and Lower Desires - McGoun, A. F. (Quarterly Journal of Economics, 1923)
Consumption may affect capacity for production. — Satisfaction may be increased by increasing goods, or desires for available goods, 292. — Unsatisfied desire an evil, 293. — Definition of necessaries, 297. — Desire for them ultimately diminishes scarcity, 298. — The time element, 298. — The interests of other people, 299. — High desires increase efficiency, foresight, and altruism, 300.